THE EFFECT OF SOCIAL MEDIA MARKETING ON PURCHASING DECISIONS FOR SKINTIFIC PRODUCTS IN DENPASAR CITY WITH BRAND IMAGE AS A MEDIATING VARIABLE - Parwita, Gde Bayu Surya; Puspitawati, Ni Made Dwi; Darki, Ni Putu Uma Shintya Dewi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2025)
The emergence of counterfeit skincare products containing harmful ingredients has created serious challenges for the beauty industry, including Skintific. Consumers who are increasingly savvy and critical of the products they use have forced Skintific to think hard about how to maintain its business with various strategies, including marketing strategies to increase consumer purchasing decisions for skincare products, especially Skintific products. This study aims to determine and analyze the influence of social media marketing on purchasing decisions with brand image as a mediating variable for Skintific skincare products in Denpasar City. The sample size used was 120 respondents who are users of Skintific skincare products in Denpasar City, Bali, with sampling using Nonprobability Sampling with the Snowball Sampling method. Data was collected using a Likert scale questionnaire and processed using SEM-PLS. The results of the study prove that social media marketing has a positive effect on purchasing decisions, social media marketing has a positive effect on brand image, brand image has a positive effect on purchasing decisions, and brand image is able to mediate the effect of social media marketing on purchasing decisions.